Influence of balancing‐side occlusal interference on smoothness of working‐side condylar movement and intra‐articular space in chewing efforts. (27th August 2014) - Yashiro, K.; Yamamoto, K.; Takada, K.; Murakami, S.; Uchiyama, Y.; Furukawa, S.
Summary Response of temporomandibular joint (TMJ) articulation adapting to occlusal alteration has been sparsely known. For 10 healthy adults with acceptably good occlusion, an artificial occlusal interference (OI) was introduced to the lower molar on the balancing side of unilateral chewing. Subjects were asked to chew a gum on their preferred side. The chewing jaw movements with/without the OI were recorded using a video‐based optoelectronic system. The mandibular movements were generated in each individual's TMJ model reconstructed by magnetic resonance images. The smoothness of local condylar point movements towards the normal direction of the condylar surface and interarticular space on the working side was measured. Overall, the smoothness of condylar point movements in the closing phase was impaired immediately after introduction of the OI. In the intercuspal phase, the OI increased the joint space. After about 60 chewing cycles, the movement smoothness and joint space began to recover. These findings suggest that OI on the balancing side induced irregular stress field translation on the working‐side condylar surface followed by acute recovery process.